1993
DOI: 10.1002/jbm.820270103
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of collagen fixation with polyepoxy fixatives

Abstract: A new biomaterial has been developed by fixing native collagen with a polyepoxy compound (PC) fixative. In this study, bovine internal thoracic arteries were fixed with PC under various conditions to help understand the kinetics of the collagen-PC reactions and optimize the fixation process. At predetermined time intervals, small samples were cut from the arteries to determine the quantities of the remaining unreacted amino acids in the collagen. Temperature, concentration, and solution pH were among the key p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…19 The technique has proved valuable in assessing the efficiency and density of artificially induced intermolecular crosslinks, produced by various chemical tanning agents, on a number of tissues. [20][21][22][23] The shrinkage temperature of cortical bone collagen has been shown to decline with age in rats 11 and in humans, healthy or otherwise. 4 A concomitant decrease in the biochemical stability of a tissue 4 implies that bone collagen becomes less stable with age.…”
Section: Collagen's Thermal Stabilitymentioning
confidence: 99%
“…19 The technique has proved valuable in assessing the efficiency and density of artificially induced intermolecular crosslinks, produced by various chemical tanning agents, on a number of tissues. [20][21][22][23] The shrinkage temperature of cortical bone collagen has been shown to decline with age in rats 11 and in humans, healthy or otherwise. 4 A concomitant decrease in the biochemical stability of a tissue 4 implies that bone collagen becomes less stable with age.…”
Section: Collagen's Thermal Stabilitymentioning
confidence: 99%
“…17 Further, it has been observed that the PEGs can abrogate the immunogenicity of proteins and are capable of preserving their biological properties. 18,19 PEGs are used for improving the biocompatibility of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, crosslinking reagents have been used to strengthen the mechanical properties of porous collagen and to slow down its degradation rate. However, most crosslinking reagents are cytotoxic and thus cannot be used for tissue regeneration [19][20][21][22][23][24][25][26]. Hence, the development of a novel type of collagen that can address the previous limitation is important.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, crosslinking reagents such as glutaraldehyde, carbodiimide, and epoxy compounds, among others, have been used to slow down the degradation rate of porous collagen. However, most crosslinking reagents are cytotoxic and are not suitable for tissue regeneration [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%